The home environment in a nationwide sample of multi‐family buildings in Sweden: associations with ocular, nasal, throat and dermal symptoms, headache, and fatigue among adults - Yang, Qin; Wang, Juan; Norbäck, Dan (Indoor air, 2021)
Risk factors at home for ocular, nasal, throat and dermal symptoms, headache, and fatigue were studied in a nationwide questionnaire survey in Sweden, the BETSI study in 2006. Totally, 5775 adults from a stratified random sample of multi‐family buildings participated. Associations between home environment factors and weekly symptoms were analyzed by multi‐level logistic regression. In total, 8.3% had ocular symptoms; 11.9% nasal symptoms; 7.1% throat symptoms; 11.9% dermal symptoms; 8.5% headache and 23.1% fatigue. Subjects in colder climate zones had more mucosal and throat symptoms but less fatigue and ocular symptoms. Rented apartments had poorer indoor environment than self‐owned apartments. Those living in buildings constructed from 1961 to 1985 had most symptoms. Building dampness, mold and mold odor were risk factors, especially headache and ocular symptoms. Lack of mechanical ventilation system was another risk factor, especially for headache. Environmental tobacco smoke (ETS), electric radiators, and crowdedness were other risk factors. Oiled wooden floors, recent indoor painting, and new floor materials were negatively associated with symptoms. In conclusion, building dampness, mold, poor ventilation conditions, crowdedness, ETS, and emissions from electric radiators in apartments in Sweden can increase the risk of ocular, nasal, throat and dermal symptoms, headache, and fatigue.